2018
DOI: 10.1085/jgp.201812064
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of the voltage-sensing phosphatase controls its voltage-sensing and catalytic activity

Abstract: The Ciona intestinalis voltage-sensing phosphatase (Ci-VSP) was not thought to multimerize. Rayaprolu et al. show that Ci-VSP exists as a dimer and that this interaction lowers the voltage dependence of activation and alters substrate specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(58 citation statements)
references
References 50 publications
9
49
0
Order By: Relevance
“…However, the apparent enzymatic activity of VSP will also depend on the level of its surface expression ( Murata and Okamura, 2007 ). In Xenopus oocytes, the expression level can be controlled by regulating the amount of injected RNA ( Rayaprolu et al, 2018 ). On the other hand, the protein expression level in transfected cultured cells often varies from cell to cell dependent on the copy number of introduced plasmids.…”
Section: Resultsmentioning
confidence: 99%
“…However, the apparent enzymatic activity of VSP will also depend on the level of its surface expression ( Murata and Okamura, 2007 ). In Xenopus oocytes, the expression level can be controlled by regulating the amount of injected RNA ( Rayaprolu et al, 2018 ). On the other hand, the protein expression level in transfected cultured cells often varies from cell to cell dependent on the copy number of introduced plasmids.…”
Section: Resultsmentioning
confidence: 99%
“…Second, a single VSD regulates a single CCR, in contrast with VGICs, in which four homologous units (repeat or subunit) assemble to regulate a central pore gate in a complex manner. Although a recent study suggested that VSPs can form dimers with high density expression and that dimeric VSPs exhibit slightly different molecular properties than those of monomers, the basic nature of voltage-dependent enzyme activity is innate to monomers (Rayaprolu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…PH domains are well known proteins that bind specifically to certain PIPs (38-40). We chose PH domains from tandem PH domain containing protein 1 (TAPP) and phospholipase C (PLC) because they bind specifically to phosphatidylinositol-3,4-bisphosphate [PI(3,4)P 2 ] and PI(4,5)P 2 , respectively, allowing us to monitor both 5- and 3-phosphatase activities (12,14,41,42). To follow PI(3,4)P 2 , we used the biosensor fTAPP that utilizes the PH domain from TAPP flanked by an N-terminal CFP and C-terminal YFP, while the whole sensor is anchored to the membrane through a prenylation site at the C-terminus (Fig 6B) (41-43).…”
Section: Resultsmentioning
confidence: 99%
“…This small signal is expected because it has been previously shown that a low level of endogenous Xl-VSP activity is present in X . laevis oocytes (14,22,41,42,44). Interestingly, the same fTAPP experiment with Xl-VSP2 only showed a FRET increase (Fig 6C, green) even when we extended the voltage pulse to 60 seconds (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation